Induction of the reactive chlorine-responsive transcription factor RclR in Escherichia coli following ingestion by neutrophils. Issue 1 (22nd December 2020) - Königstorfer, Andreas; Ashby, Louisa V; Bollar, Gretchen E; Billiot, Caitlin E; Gray, Michael J; Jakob, Ursula; Hampton, Mark B; Winterbourn, Christine C
ABSTRACT: Neutrophils generate hypochlorous acid (HOCl) and related reactive chlorine species as part of their defence against invading microorganisms. In isolation, bacteria respond to reactive chlorine species by upregulating responses that provide defence against oxidative challenge. Key questions are whether these responses are induced when bacteria are phagocytosed by neutrophils, and whether this provides them with a survival advantage. We investigated RclR, a transcriptional activator of the rclABC operon in Escherichia coli that has been shown to be specifically activated by reactive chlorine species. We first measured induction by individual reactive chlorine species, and showed that HOCl itself activates the response, as do chloramines (products of HOCl reacting with amines) provided they are cell permeable. Strong RclR activation was seen in E. coli following phagocytosis by neutrophils, beginning within 5 min and persisting for 40 min. RclR activation was suppressed by inhibitors of NOX2 and myeloperoxidase, providing strong evidence that it was due to HOCl production in the phagosome. RclR activation demonstrates that HOCl, or a derived chloramine, enters phagocytosed bacteria in sufficient amount to induce this response. Although RclR was induced in wild-type bacteria following phagocytosis, we detected no greater sensitivity to neutrophil killing of mutants lacking genes in the rclABC operon. Abstract : The reactive chlorine-responsive transcription factor RclR is induced in E. coli following ingestion by neutrophils.